O uso da taxonomia do solo para o desenvolvimento do raciocínio clínico de estudantes de medicina - Resende, Patrícia Teixeira de (2023)
Introduction: The clinical reasoning ability is a complex cognitive activity that develops in progressive stages. The use of teaching strategies based on learning taxonomies has the potential to contribute to their development. However, most studies on clinical reasoning have evaluated strategies for acquiring disease scripts in medical students, and little discussion is found on the cognitive processes involved in acquiring this skill. The SOLO Taxonomy proposes a categorization of the learning structure that closely resembles the processes described for the development of clinical reasoning and therefore has the potential to contribute to the systematization of educational strategies for this purpose. Objective: The aim of this research was to develop and test a methodology for teaching clinical reasoning based on the assumptions of the SOLO Taxonomy, which proposes that learning takes place in successive and progressive stages of cognitive structural complexity. Materials and Methods: A longitudinal, descriptive study with a quantitative approach, with 5 phases: Phase 1 (pre-test): resolution of 6 clinical cases (3 of chest pain, 3 of pelvic pain); Phase 2 and 3 (intervention): development of the methodology for teaching clinical reasoning guided by the SOLO Taxonomy compared to the lecture; Phase 4 (immediate post-test) and Phase 5 (delayed post test, after one week). To train clinical reasoning, tasks were developed based on the assumptions of the SOLO Taxonomy, with a structure of increasing complexity, using as a theoretical reference the studies on instructional activities published for the development of clinical reasoning, and others described for the SOLO Taxonomy. Results: The tool used was able to improve the students’ diagnostic accuracy, with no significant difference compared to the theoretical lecture. Conclusion: The strategy can be considered for the development of clinical reasoning in health courses since it promotes learning and is an active teaching methodology.